Flood Vulnerability Analysis of Pashchim Champaran, India Using Geographic Information System-Based Overlay and Scoring Methods - Shubham, Kumar (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2025)
Pashchim Champaran, a district situated in the state of Bihar, India, is the largest district in the state, spanning an area of 5,228 km2 and belonging to the Tirhut Division. The administrative center of the district is located in Bettiah. As a flood-prone region within the state of Bihar, Pashchim Champaran frequently experiences flooding due to its proximity to major rivers and the unique geographical characteristics of the area. This research employs a Geographic Information System-based overlay and scoring methodology to assess the flood vulnerability of Pashchim Champaran. Parameters such as slope, elevation, soil type, rainfall, land cover, and river density are assigned scores and weights based on their respective classifications. These weighted scores are then overlaid using ArcGIS to generate a flood vulnerability map. The findings reveal that approximately 63% of the region is classified as having high or very high vulnerability to flooding, indicating the urgent necessity for comprehensive flood mitigation strategies in the area. The resulting map categorizes the region into varying vulnerability levels, providing valuable insights for policymakers and stakeholders in disaster preparedness and resource allocation for flood risk reduction in Pashchim Champaran.